Maverick Mark : The Untamed First Gospel - Thurston, Bonnie Bowman (Book collections on Project MUSE., 2013)
Somewhere along the way, says Bonnie Thurston, the wild unlikelihood of the Christian message has been reined in and made to fit more conventional categories of thought. That it is good and moral to be Christian we understand. That it is feral and almost uncontrollably countercultural is something that has been largely forgotten or suppressed. This taming has been especially effective in the case of the first gospel. In Maverick Mark, Thurston sets out to rediscover the radicalism of Mark's original message. Thurston focuses on Mark's conception of discipleship, economic justice, and personal lifestyle. She demonstrates that this gospel raises fundamental questions about some common contemporary Christian assumptions. This is an accessible introduction to Mark, ideal for interested adult readers of all kinds, which incorporates the most reliable and up-to-date Scripture scholarship.